Contributing to Children’s Early Comprehension of Emotions: A Picture Book Approach - LaForge, Christian; Perron, Mélanie; Roy-Charland, Annie; Roy, Emilie Myriam; Carignan, Isabelle (Canadian Journal of Education/Revue canadienne de l’éducation, 2018)
Previous studies have suggested that children’s emotion comprehension begins to develop in the early stages of childhood and has been linked to prosocial behaviours, displays of empathy, and better interpersonal relationships, to name a few. However, children’s levels of emotion comprehension do not develop at the same rhythm, due to both environmental and biological factors. There are a few interventions that can help children in their development of emotion understanding, but these interventions are not readily accessible (e.g., due to cost, availability, duration). For example, the School Matters in Lifeskills Education Program (SMILE) is a theoretically based program aimed at improving children’s emotion comprehension. Unfortunately, since, for instance, it requires rigorous training to be administered, it is not accessible to all. To address some of the issues with previous programs, the current study examined the use of shared book reading and the effectiveness of picture books created on current theories and models of children’s emotion comprehension. Eighteen preschoolers were divided into an experimental and a control group. Over the course of multiple exposures to the experimental treatment, results revealed a significant gain for the experimental group compared to the control group. These results are promising by showing that a simple shared book reading approach can contribute to the development of emotion comprehension without requiring special training or expertise.